PENGEMBANGAN STRATEGI LABORATORIUM UJI PT XYZ : STRATEGY DEVELOPMENT FOR TEST LABORATORY OF PT XYZ - Adi Mulyadi; Kirbrandoko; Sahara (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Increasing population, human welfare, awareness of product safety in order to meet the regulation requires a reliable test laboratory. Competition among service-laboratory made PT XYZ as a test laboratory faces competition with other laboratories. This research aimed to analyze the strategy development of PT XYZ in order to 1) analyze the company’s internal and external factors in the service laboratory industry, 2) determine company alternative strategies, 3) recommend the best strategy from these alternatives. The study used IFAS (Internal Factor Analysis Summary), and EFAS (External Factor Analysis Summary), IE (Internal External), and SWOT (Strengths Weakness Opportunities Threats) matrix. The internal analysis found five factors respectively, for strengths and weaknesses, while the external factor found five factors, respectively for opportunities and threats. The scores from IFAS and EFAS matrix analysis were of 2,785 and 2,583, respectively. These scores represented the company’s position in the IE matrix, which was on cell V. Thus, the related strategy was hold and maintain. The formulated alternative strategies were market penetration, product development, and service differentiation. Keywords: alternative strategies, EFAS, IE, IFAS, service laboratory, SWOT Abstrak: Populasi yang meningkat, kesejahteraan, kesadaran akan produk yang aman, dan untuk memenuhi kebutuhan regulasi diperlukan suatu laboratorium uji yang handal. Persaingan di bidang laboratorium layanan menjadikan PT XYZ sebagai laboratorium penguji harus mampu bersaing dengan laboratorium lain. Penelitian ini bertujuan 1) menganalisis faktor internal dan eksternal perusahaan dalam industri laboratorium jasa, 2) menentukan strategi alternatif yang dapat dilakukan oleh perusahaan, 3) merekomendasikan strategi terbaik dari berbagai alternatif. Metode yang digunakan pada penelitian ini adalah IFAS (Internal Factor Analysis Summary) dan EFAS (External Factor Analysis Summary), IE (Internal External), dan matriks SWOT (Strengths Weakness Opportunity Threaths). Analisis internal menunjukkan 5 faktor kekuatan dan 5 faktor kelemahan, sedangkan faktor eksternal menunjukkan 5 faktor peluang dan 5 faktor ancaman. Analisis matriks IFAS dan EFAS menunjukkan skor 2,785 dan 2,583. Skor ini menunjukkan bahwa posisi perusahaan pada matriks IE berada di sel V. Strategi yang tepat dalam kuadran ini adalah menjaga dan mempertahankan. Strategi alternatif yang dirumuskan untuk perusahaan adalah penetrasi pasar, pengembangan produk dan strategi diferensiasi layanan. Kata kunci: alternatif strategi, IFAS, IE, EFAS, laboratorium jasa, SWOT